ETHNOBOTANICAL STUDY OF MEDICINAL PLANTS USED BY IKARE AND IPE PEOPLE OF AKOKO IN ONDO STATE, NIGERIA - Giwa, A.; Odofin, W.; Aladele, S.; Daramola, B. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The aim of this study was to investigate the medicinal uses, cultivation and remedies of various indigenous plants, which are commonly used by local people. Ethnobotanical study was carried out in two notable villages in Akoko area of Ondo State (Ikare and Ipe) respectively. The information gathered was obtained through interviewing the herbalist and traditional medicine practitioners. In this study, 68 plant species which are commonly used among the people to cure diseases, were presented. Herbarium specimens were also carefully preserved for detail study. This study helped to preserve the information and skill acquired by processes of trial and error the centuries by these people.